PENGARUH KOMPETENSI KEPRIBADIAN DAN KECERDASAN EMOSIONAL TERHADAP KINERJA GURU SMP NEGERI 13 BALIKPAPAN - jurnalpps pps; Wadi Reina Anggraini; C. Sri Hartati; Woro Utari (Prodi Magister Manajemen Universitas Wijaya Putra, 2021)
This research is the result of research which describes how much personality competence and emotional intelligence have an effect on improving teacher performance at SMP Negeri 13 Balikpapan. The background of this research is because based on the results of observations it shows an increase from year to year, the achievement of SMP Negeri 13 Balikpapan both academically and non-academically is not optimal. After looking at several indicators, this study focuses on looking at the influence of personality competence and emotional intelligence on teacher performance at SMP Negeri 13 Balikpapan. This research uses quantitative research methods. The research subjects were all teachers who served at SMP Negeri 13 Balikpapan. The results showed that personality competence and emotional intelligence had a significant effect on teacher performance at SMP Negeri 13 Balikpapan.